Neighbourhood: reverberations of an idea in a moving Lisbon - Marluci, Menezes (2019)
The article addresses the notion of ‘neighbourhood’ as an important symbolic resource of the imaginary of Lisbon today, not only  confirming the transformative continuity that the city is “a city of neighbourhoods”, but also influencing the everyday reality of  these neighbourhood places. For this purpose, a re-visitation of the notion of neighbourhood in literature is carried out. It is then  exemplifies, through certain cases, some resources to the neighbourhood notion and its re-signification of the concept, seeking to  observe some of the contemporary problems of the city and, as such, its neighbourhoods.